Pelatihan Display Produk untuk Bazaar - Suhariadi, Fendy; Herachwati, Nuri; Agustina, Tri Siwi; Maghfira, Ayya; Sofwani, Alifa Rifdatus; Amalia, Shafyra (Journal Pemberdayaan Masyarakat Indonesia, 2022)
Koperasi Srikandi Roda Jatim is a cooperative consisting of women who work as Ojek Online (OJOL) drivers in Surabaya city. As an effort to prosper the members, this cooperative actively participates in the bazaar. However, it was found that the bazaar activities that were followed were not balanced with product sales, meaning that the product was empty of buyers. The target audience of this activity is cooperative members who live in Surabaya and require special attention such as having the status of a single parent, belonging to a Low Income Society (MBR), having children with special needs or disabilities. This community service activity is the implementation of SDG's no. 5 on gender equality and SDG's no. 8 on decent employment opportunities and economic growth. The problem experienced by partners is the lack of knowledge and skills of product arrangement display when participating in the exhibition. The purpose and hope of this activity is that the members of the Srikandi Roda Jatim Cooperative in Surabaya City have the knowledge and skills to displays when participating in the bazaar in the hope that the products on display can attract the attention of visitors and are interested in buying so that the standard of living and welfare of the cooperative members can be realized.